2014
DOI: 10.9790/487x-16543339
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Work Attitude Amongst ‘Y’ Generation University Evening Students in Kenya (A Case of Africa Nazarene University)

Abstract: There are three generations active in the work force, that is Baby Boomers (born before 1950), Generation X (born between 1950s and 1980s), and Generation Y (born in the late 1980s to 2000). The purpose of this study was to determine factors influencing work attitudes amongst the Y generation. The specific objectives of the study were to identify variables that affect generation Y attitude towards work and decompose the identified variables into factors that can be subjected to further analysis. Data was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Hiring Millennials, many companies realized that this generation came with different attitudes and work habits that need adaptation with existing cultures. Employing young talents who have just left college is a challenging process for the company because it has changed the culture of the company lately (Kamau, et al, 2014). Therefore, problems that arise such as the gap between generations and the number of Generation Y employees leaving their jobs for career advancement are new concerns for today's companies (Stichnote & Crow, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hiring Millennials, many companies realized that this generation came with different attitudes and work habits that need adaptation with existing cultures. Employing young talents who have just left college is a challenging process for the company because it has changed the culture of the company lately (Kamau, et al, 2014). Therefore, problems that arise such as the gap between generations and the number of Generation Y employees leaving their jobs for career advancement are new concerns for today's companies (Stichnote & Crow, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Five questions were adapted to reveal LO (Baker & Sinkula, 1999). Seven questions allowed to calculate employee attitude (Kamau et al, 2014). Five questions tackled measuring PSB (Bettencourt et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…FLE's attitude is an incomplete and debatable topic amongst researchers, and many researchers are investigating the influence of organizational culture on FLE's attitude in the service sector (Awwad & Agti, 2011). A study on attitude toward work in different generations, including baby boomers (born before 1950), generation X (born between the 1950s and 1980s), and generation Y (born in the late 1980s to 2000) analyzed by (Kamau et al, 2014). Few studies have reported corporate culture as one of the most substantial factors influencing FLE's attitude (Cherian et al, 2021;Makumbe, 2022;Abbas & Dogan, 2022).…”
Section: Employee Attitudementioning
confidence: 99%
“…Another name given to this generation is "the trophy kids", due to the fact they have been raised in an environment in which they have received awards for the simplest things (Crampton & Hodge, 2009). The work of Kamau et al (2014) argues that one of the characteristics of millennials is that they do not comply with rules at work and prefer to do things their own way. In other words, the millennials want to have a degree of job autonomy in their work.…”
Section: The Millennialsmentioning
confidence: 99%
“…As a consequence, the millennials question every rule that is made in a company, and believe that rules are made to be broken (Gursoy et al, 2008). In their quantitative study among part-time students, Kamau et al (2014) found that millennials seek freedom in their jobs and are very self-assertive. As a consequence, they do not feel the need to consult others and believe that their way is the right way.…”
Section: The Millennialsmentioning
confidence: 99%